2002
DOI: 10.1002/jmv.10245
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival and virus production in human primary macrophages infected by human immunodeficiency virus

Abstract: The role of macrophages in the pathogenesis and progression of human immunodeficiency virus (HIV)-related infection is substantiated by in vitro and in vivo evidence. The unique ability to survive HIV infection and produce viral particles for long periods is postulated. Detailed studies of this phenomenon are lacking. The dynamics of HIV-1 replication and cumulative virus production was studied in long-term cultures of macrophages in the presence or in the absence of antiviral drugs. Multiply spliced and unspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
86
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 53 publications
5
86
0
Order By: Relevance
“…We further demonstrate that, compared to macrophages maintained in the absence of M-CSF, acutely infected cells that are constitutively maintained in the presence of M-CSF displayed significantly diminished antiviral potency (EC 50 , 0.03 to 0.40 M versus 0.4 to 9.42 M, respectively). These data are confirmed by previous studies (2,8,10) on the antiviral potencies of NRTIs in chronically infected macrophages and are also in agreement with reports demonstrating the potencies of protease inhibitors against chronically and acutely infected lymphocytes and macrophages (10). The cellular-pharmacology studies also demonstrated for the first time that the intracellular concentration of RAL was significantly lower in macrophages than in lymphocytes, independent of the activation state.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We further demonstrate that, compared to macrophages maintained in the absence of M-CSF, acutely infected cells that are constitutively maintained in the presence of M-CSF displayed significantly diminished antiviral potency (EC 50 , 0.03 to 0.40 M versus 0.4 to 9.42 M, respectively). These data are confirmed by previous studies (2,8,10) on the antiviral potencies of NRTIs in chronically infected macrophages and are also in agreement with reports demonstrating the potencies of protease inhibitors against chronically and acutely infected lymphocytes and macrophages (10). The cellular-pharmacology studies also demonstrated for the first time that the intracellular concentration of RAL was significantly lower in macrophages than in lymphocytes, independent of the activation state.…”
Section: Discussionsupporting
confidence: 91%
“…These factors create many distinct and often concomitant microenvironments with heterogeneous exposures to extracellular drug concentrations relative to systemic CD4 ϩ T lymphocytes. Macrophages are a target for early infection (1,3,8) and are present in multiple sites of primary transmission, including the gut and genital tract (1,2,4). Infection in macrophages often results in subpopulations of latent infection, which can occur across any tissue or organ containing these cells, such as the brain or lymphoid tissues, rendering them a ubiquitous source for reactivation of virus later in disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability of such an approach will depend on the identification of suitable receptors of potential medical relevance, e.g., the use of macrophage-associated carbohydrate receptors (14,39) to treat macrophage-associated diseases such as lysosomal storage disease (40) or viral infections (41). Moreover, the additional benefit of rhamnose targeting (and hence double targeting) in the current liver LEAPT system might be lost in other tissue͞cell systems, necessitating a reliance on passive small-molecule mechanisms such as pinocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their longevity and relative resistance to the cytopathogenic effect of HIV-1, macrophages contribute to the establishment of viral reservoirs and are able to transmit the virus to other target cells (2)(3)(4). HIV-1 infection of macrophages also affects their functions in innate and adaptive responses to pathogens (5).…”
mentioning
confidence: 99%